Володимир Іполитович Липський (до 150-річчя від дня народження) - Крецул, Н.І.; Федорончук, М.М. (Український ботанічний журнал, 2013)
В статье прослеживается научный путь и научно-организационная деятельность известного ботаника, флориста, систематика, организатора работы ботанических садов, академика и президента (1922—1928) Всеукраинской академии наук, члена-корреспондента АН СССР В.И. Липского. The article traces the scientific path and scientific-organizational activity of the well-known botanist, florist, taxonomist, convener of the Botanical gardens, Academician and President (1922—1928) of the Ukrainian Academy of Sciences, corresponding mem ber of the Academy of Sciences of the USSR.